The Effect of Styrofoam as an Additive to AC-WC Mixture in Batu Sungai Tetean, Mamasa Regency - Samudra Tandiabang; Alpius; Elizabeth (Paulus Civil Engineering Journal, 2022)
Roads are a very important need for the community of Mamasa Regency, so research is carried out on the Tetean river stone whether it is suitable for use as pavement for Asphalt Concrete-Wearing-Course mixture. The methodology in this research is to perform a series of tests on the characteristics of coarse, fine aggregate, filler, and asphalt then design the composition of the AC-WC mixture and Marshall immersion test for the characteristics of the mixture. The results showed that the characteristics of the AC-WC mixture using Tete River Stone and styrofoam as added materials through the Marshall test obtained the mixed characteristic values, namely stability, flow, VIM, VMA, and VFB all met the General Specifications of Highways 2018. The effect of adding styrofoam to the mixture AC-WC is able to fill voids in the mixture which makes the voids smaller, making the bonds between the aggregates stronger so that with the addition of Styrofoam the mixture becomes more watertight/resistant to water, weather and traffic loads.